2015
DOI: 10.1016/j.adolescence.2015.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Identity processes and statuses in post‐Soviet Georgia: Exploration processes operate differently

Abstract: Identity formation is one of the main developmental tasks of emerging adulthood. Based on quantitative data on a five-dimensional model of identity formation, we concluded that the identity formation process has some different features in the Republic of Georgia than it does in many Western countries. Results obtained from young Georgian adults (N = 295, 82.6% female) yielded four exploration processes instead of three, which is in line with the recent Swiss findings. A key difference between Georgia and the W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
58
3
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(88 citation statements)
references
References 70 publications
11
58
3
8
Order By: Relevance
“…First, latent profile analyses yielded five identity profiles identified also in previous studies (e.g., Schwartz et al, 2011). It is worthy of note that in this study the achievement profile showed relatively weak exploration of alternatives, as has been observed in other studies (Skhirtladze, Javakhishvili, Schwartz, Beyers, & Luyckx, 2016).…”
Section: Discussionsupporting
confidence: 82%
“…First, latent profile analyses yielded five identity profiles identified also in previous studies (e.g., Schwartz et al, 2011). It is worthy of note that in this study the achievement profile showed relatively weak exploration of alternatives, as has been observed in other studies (Skhirtladze, Javakhishvili, Schwartz, Beyers, & Luyckx, 2016).…”
Section: Discussionsupporting
confidence: 82%
“…Higher scores suggest more severe depressive symptomatology. The BDI has been used in previous studies of the Georgian population [16,17]. …”
Section: Methodsmentioning
confidence: 99%
“…( 2015) and Skhirtladze et al (2015) have independently found that in-depth exploration can be both positively and negatively related to commitment. They therefore proposed to subdivide in-depth exploration in two subcategories: commitment reconsideration, which is related to decreases in commitment; and reflective in depth exploration, which is related to increases in commitment.…”
Section: Experiences Versus Explorationmentioning
confidence: 99%